2013
DOI: 10.1073/pnas.1219995110
|View full text |Cite
|
Sign up to set email alerts
|

Genetic deletion of Rnd3 results in aqueductal stenosis leading to hydrocephalus through up-regulation of Notch signaling

Abstract: Rho family guanosine triphosphatase (GTPase) 3 (Rnd3), a member of the small Rho GTPase family, is involved in the regulation of cell actin cytoskeleton dynamics, cell migration, and proliferation through the Rho kinase-dependent signaling pathway. We report a role of Rnd3 in the pathogenesis of hydrocephalus disorder. Mice with Rnd3 genetic deletion developed severe obstructive hydrocephalus with enlargement of the lateral and third ventricles, but not of the fourth ventricles. The cer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
70
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 46 publications
(72 citation statements)
references
References 20 publications
2
70
0
Order By: Relevance
“…15 Given the fact that there are more than 600 putative E3 ligases in humans, 55 our future study will investigate whether Rnd3 directly binds to an E3 ligase functioning as an ancillary protein, or interacts with arrestin family members.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15 Given the fact that there are more than 600 putative E3 ligases in humans, 55 our future study will investigate whether Rnd3 directly binds to an E3 ligase functioning as an ancillary protein, or interacts with arrestin family members.…”
Section: Discussionmentioning
confidence: 99%
“…13, 14 We recently uncovered a Rho kinase-independent function of Rnd3, and reported that genetic deletion of Rnd3 led to aqueductal stenosis in mouse brains through upregulation of Notch signaling. 15 Two studies found that Rnd3 was indispensable in mouse neuron development, 16, 17 suggesting Rnd3 is involved in much broader biological functions besides its inhibitory effect on Rho kinase. In this study, we provide evidence to reveal a function of Rnd3, in which Rnd3 regulates the β 2 AR-PKA signaling pathway.…”
Section: Introductionmentioning
confidence: 99%
“…Early pattern formation genes such as SHH, ZIC2, PAX6, and WNT1, neuronal path-finding genes such as L1CAM, genes related to cortical development such as POMT1, and those related to growth regulation such as PIK3CA and AKT3 have been implicated. 1,3,7,10,29,52,53,72,84,85,91,103,122 Developmental disorders presenting with hydrocephalus include neural tube disorders, forebrain and hindbrain developmental disorders, brain growth disorders, and cortical malformations. Alterations in the choroid plexus, ependyma, aqueduct, ventricles, and extraaxial spaces can also lead to hydrocephalus.…”
Section: Theme 1: Causes Of Hydrocephalus Geneticsmentioning
confidence: 99%
“…First, RhoE limits the proliferation of basal progenitors at the SVZ, by a mechanism that does not depend on the control of actin depolymerisation but on suppression of cyclin D1 translation (Pacary et al 2013). On the other hand, RhoE deletion results in hyperplasia of ependymal cells in the aqueduct by increasing Notch signaling activity (Lin et al 2013). The later work shows that ependymal cells hyperplasia produces aqueductal stenosis and subsequent hydrocephalus (Lin et al 2013), a phenotype that our results confirm.…”
Section: Rhoe Is Required For a Proper Svz Developmentmentioning
confidence: 99%
“…On the other hand, RhoE deletion results in hyperplasia of ependymal cells in the aqueduct by increasing Notch signaling activity (Lin et al 2013). The later work shows that ependymal cells hyperplasia produces aqueductal stenosis and subsequent hydrocephalus (Lin et al 2013), a phenotype that our results confirm. Nevertheless, the inhibition of cell proliferation is probably cell-type specific since, otherwise, RhoE null brains would show a general increased number of cells and, on the contrary, they are smaller than the wild types.…”
Section: Rhoe Is Required For a Proper Svz Developmentmentioning
confidence: 99%